2024
DOI: 10.1101/2024.01.26.577389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persister cancer cells are characterized by H4K20me3 heterochromatin that defines a low inflammatory profile

Valentina Ramponi,
Laia Richart,
Marta Kovatcheva
et al.

Abstract: SUMMARYAnti-cancer therapies may induce proliferative arrest in cancer cells in the form of senescence or drug-tolerant persistency, the latter being a reversible arrest with similarities to embryonic diapause. Here, we use mTOR/PI3K inhibition to develop and characterize a model of persistency/diapause-like arrest in human cancer cells of various origins. We show that persister and senescent cancer cells share an expanded lysosomal compartment and hypersensitivity to BCL-XL inhibition. However, persister cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 110 publications
(176 reference statements)
0
1
0
Order By: Relevance
“…A remarkable recent finding has been the observation that cancer DTP cells and embryonic diapause cells share an extensive transcriptional profile 9,47,48 . Recently, Rehman et al identified a distinctive embryonic diapause gene signature which significantly correlated with cancer DTP cells.…”
Section: Resultsmentioning
confidence: 99%
“…A remarkable recent finding has been the observation that cancer DTP cells and embryonic diapause cells share an extensive transcriptional profile 9,47,48 . Recently, Rehman et al identified a distinctive embryonic diapause gene signature which significantly correlated with cancer DTP cells.…”
Section: Resultsmentioning
confidence: 99%